Neuropsychological Functioning and Temperament Traits in a Czech Sample of Children and Adolescents at Familial Risk of Bipolar Disorder - Goetz, Michal; Novak, Tomas; Viktorinova, Michaela; Ptacek, Radek; Mohaplova, Marketa; Sebela, Antonin (Frontiers in Psychiatry, 2019)
Background: Although a positive family history is the strongest predictor for bipolar disorder (BD), most offspring of BD parents (BO) will not develop the disorder. Identification of vulnerability markers for BD is essential for specific individual risk estimation. Impairments in cognitive functioning and the presence of specific temperament traits are considered promising candidates. Methods: Sixty-three BO (48% female; 11.8±3.3 y) and 54 control offspring (CO; 44% female; 12.3±3.2 y) comparable in sex (p=.4) and age (p=.4) were enrolled. Detection of current sub/threshold mood symptoms by the Kiddie Schedule for Affective Disorders and Schizophrenia and General Behavior Inventory was applied to separate BO into ultrahigh-risk (UHR) and high-risk (HR) subgroups. Cognitive functions were tested by the Developmental Neuropsychological Assessment II test battery, d2 Test of Attention, and Amsterdam Neuropsychological Tasks. Temperament was assessed by the Temperament in Middle Childhood and Early Adolescent Temperament Questionnaires. Results: The BO sample consisted of 5 BD, 17 UHR and 41 HR participants. We did not observe any significant differences between the BO and CO groups or between the UHR, HR, and CO subgroups (Hedges´ g= 0.21-0.39) in cognitive functioning. The BO differed significantly in some temperament traits from the CO (g= 0.42-0.61), while the UHR subgroup exhibited lower effortful control and attention focusing than both HR and CO participants (g= 0.92-1.19). Limitations: The cross-sectional design and wide age range of the sample limited our findings. Conclusions: Neuropsychological impairment does not seem to be a trait marker of BD in the premorbid stage. Temperament with low effortful control and low attention focusing might be associated with the development of mood disorders in BO.